PERANCANGAN SISTEM PROTEKSI DAN MONITORING UNTUK GENERATOR SINKRON TIGA FASE BERBASIS ARDUINO MEGA 2560 - I Made Ari Nrartha; Ida Bagus Fery Citarsa (Jurusan Teknik Elektro Fakultas Teknik Universitas Mataram, 2019)
Three-phase synchronous generator is the main part in the power system, so needs protection and monitoring systems to ensure the safe operation. Three-phase synchronous generator faults such as overvoltage, low voltage, unbalanced voltage, excitation loss, unbalanced current, over current, single line to ground fault, double line to ground fault, three-phase fault, over heat and over speed protected by removing the generator from the system through a power breaker. After power breaker open, the prime mover and the excitation current supply are turned off, respectively. The protection and monitoring system are designed using sensors such as ACS712-20A-T current sensor, ZMPT101B voltage sensor, LM35 temperature sensor and tacho generator speed sensor. Arduino Mega 2560 is used as an ADC for sensor reading, calibrate the sensors, and sending sensors information to LCD and a Personal Computer (PC) by serial communication. Interface on PC uses Graphical User Interface on Matlab 2013a. The results show, measurement error of current sensors are 1.7%, 1.3%, 1.7%, and 1.7% for currents of phase a, b, c, and excitation, respectively. Measurement error of voltage sensors are 1.31%, 1.29%, and 1.05% for voltages of phase a, b, dan phase c, respectively. Measurement error of LM35 temperature sensor is 0.464%. Measurement error of tacho generator is 0.378%. Monitoring by Matlab GUI's shows operation condition and status of three phase synchronous generator on normal or fault condition. Relay take average time as long as 0.697 seconds to isolate generator from system if faults occur.